Inducing RNA interference in the arbovirus vector, Culicoides sonorensis - Mills, Mary K. (Insect Mol Biol, 2014)
Biting midges in the genus Culicoides are important vectors of arboviral diseases, including epizootic hemorrhagic disease, bluetongue, and likely Schmallenberg, which cause significant economic burden worldwide. Research on these vectors has been hindered by the lack of a sequenced genome, the difficulty of consistent culturing of certain species, and the absence of molecular techniques such as RNA interference (RNAi). Here, we report the establishment of RNAi as a research tool for the adult midge, Culicoides sonorensis. Based on previous research and transcriptome analysis, which revealed putative siRNA pathway member orthologs, we hypothesized that adult C. sonorensis midges have the molecular machinery needed to preform RNA silencing. Injection of control dsRNA, dsGFP, into the hemocoel 2–3 day old adult female midges resulted in survival curves that support virus transmission. DsRNA injection targeting the newly identified C. sonorensis inhibitor of apoptosis protein 1 (CsIAP1) ortholog, resulted in a 40% decrease of transcript levels and 73% shortened median survivals as compared to dsGFP-injected controls. These results reveal the conserved function of IAP1. Importantly, they also demonstrate the feasibility of RNAi by dsRNA injection in adult midges, which will greatly facilitate studies of the underlying mechanisms of vector competence in C. sonorensis.